Konsep Munâsakhât (مناسخات) Dalam Hukum Kewarisan Islam Di Indonesia - Miftahurrahmi, Intan (Lembaga Penelitian Universitas Pangeran Diponegoro Nganjuk, 2024)
Munâsakhât, or successive inheritance, is a concept in Islamic inheritance law that governs the distribution of an estate when an heir passes away before the inheritance is distributed. In Indonesia, the application of munâsakhât often presents unique complexities, particularly within the framework of positive law and the practice of religious courts. This article explores the concept of munâsakhât in Islamic inheritance law as applied in Indonesia, including its definition, legal foundations, and implementation within the national legal system. By analyzing relevant literature and court decisions, the study aims to provide a comprehensive understanding of munâsakhât and its implications for inheritance law practices in Indonesia. The findings highlight how Islamic jurisprudence addresses complex inheritance scenarios and offers insights into harmonizing Islamic principles with Indonesia’s pluralistic legal system, thus facilitating equitable inheritance distribution in accordance with both religious teachings and state regulations.